2019
DOI: 10.3892/mmr.2019.9875
|View full text |Cite
|
Sign up to set email alerts
|

Piperazine ferulate ameliorates the development of diabetic nephropathy by regulating endothelial nitric oxide synthase

Abstract: Diabetic nephropathy (DN) is among the most common complications of diabetes mellitus. The disorder is associated with a decrease in the activity of the nitric oxide synthase/nitric oxide system. Piperazine ferulate (PF) is widely used for the treatment of kidney disease in China. The aim of the present study was to examine the effects of PF on streptozotocin (STZ)-induced DN and the underlying mechanism of this process. STZ-induced diabetic mice were intragastrically administered PF (100, 200 and 400 mg/kg/bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…A total of 45 mice were randomly divided into three groups (n=15 mice per group) as follows: A control group, a model group (DN) and the model + PF group (DN + PF group). Diabetic model mice were established according to a previously described protocol (24). PF was dissolved in 0.5% sodium carboxymethyl cellulose (CMC-Na).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 45 mice were randomly divided into three groups (n=15 mice per group) as follows: A control group, a model group (DN) and the model + PF group (DN + PF group). Diabetic model mice were established according to a previously described protocol (24). PF was dissolved in 0.5% sodium carboxymethyl cellulose (CMC-Na).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has revealed that PF reduces the levels of blood urea nitrogen and serum creatinine in rats subjected to 5/6 nephrectomy (22) and exerts anti-hypertensive effects via the activation of endothelial nitric oxide synthase (eNOS) (23). Another previous study reported that PF administration can restore the HG-induced expression of eNOS in glomerular endothelial cells and delay the development of DN (24). However, it remains unknown as to whether PF restores mesangial cell injury under hyperglycemic conditions by inhibiting p66 Shc .…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, mitochondrial reactive oxygen species can lead to eNOS uncoupling, which in turn reduces NO bioavailability, increases the formation of peroxynitrite, causes vascular relaxation and cause cardiovascular disease (Cheang et al, 2014). Hyperglycemia can also cause eNOS uncoupling (Yang et al, 2019). NO can activate plasminogen activators and matrix metalloproteinases, inhibit interstitial collagen synthesis, and downregulate TGF-β and plasminogen activator inhibitor 1 (Goligorsky, 2017).…”
Section: Matrix Metalloproteinasesmentioning
confidence: 99%
“…程洁等人 [75] . Piperazine ferulate(PF)可上调肾小球内皮细胞eNOS表达 及活性, 降低血液肌酐及尿素氮水平, 保护肾脏并延缓 DN的发生 [2] . 维生素D可上调ET-1以及ET-B受体 mRNA表达以及eNOS mRNA表达, 进而使eNOS在 Swiss Webster鼠肾脏的表达增多 [78] , 这一结果证实了 ET与NO共同调节动脉血管张力, 维持血管稳态的重 要作用.…”
Section: Enos低表达与dnunclassified
“…环境因素相互作用的严重代谢性疾病并发症 [1] , 是主 要的糖尿病(diabetes mellites, DM)微血管并发症之一, 是DM高致死率以及导致晚期肾病的的主要因素 [2] , 在全球透析疾病中占据了高达35%~40%的比率 [3] .…”
unclassified